CHARACTERIZATION OF LACTIC ACID BACTERIA AND ANTIMICROBIAL ACTIVITY IN SUI WU’U FROM BAJAWA DISTRICT, NUSA TENGGARA TIMUR, INDONESIA - AYEN, ROSALINA YULIANA; KUSDIYANTINI, ENDANG; PUJIYANTO, SRI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This research aimed to isolate, determine the characteristics of lactic acid bacteria (LAB) of Sui Wu’u from Bajawa, Nusa Tenggara Timur and identify LAB using 16S rRNA potential as antimicrobial activity against pathogenic bacteria. Methods: Sui Wu’u which has been stored for 6 months was obtained from Bajawa district, inoculated on de Man Rogosa-Sharpe Agar (Merck) + 0.5% CaCO3, purification of LAB, characterization of selected isolates, biochemical test, tolerance test for pH, viability to test temperature, and content NaCl, determination of antimicrobial action by the agar well disk diffusion method using antibiotic (Amoxicillin) as a control and as indicator bacteria (Staphylococcus aureus and Escherichia coli) and isolation of genomic 16S rRNA; molecular identification. Results: Based on research results obtained five isolates of LAB, Gram staining the LAB isolated from Sui Wu’u showed that the isolated bacteria (bacilli and coccus) are Gram-positive, catalase-negative and the isolates have tolerance of viability at temperatures of 10°C, 45°C, and 50°C and to salinitas of 4% and 6.5%. The inhibitory zone LAB isolates (2PKT) against E. coli bacteria (20 mm) and S. aureus (12 mm), and (2PKB) against E. coli bacteria (17 mm) and S. aureus (10 mm). The two selected isolates were identified as Lactobacillus fermentum strain HB bacteria with 100% identification value and 98.93% query cover and L. fermentum strain HT with 100% identification value and 99.23% query cover. Conclusion: L. fermentum from Sui Wu’u has antibacterial activity against Staphylococcus aureus and Escherichia coli.